Semiotic expression in the drawings of students of the Faculty of Fine Arts, University of Diyala (graphic analysis) (Journal of the College of Basic Education, 2022)
The research contained four axes, as the two researchers dealt with the first axis, the justification and importance of the research, and the main objective was to identify the levels of students and their expressive abilities in the art of drawing using semiotic analysis, because the research problem centered on the students’ abilities to express the formative relationships in the art of drawing in order to show the strengths and weaknesses in Their experiences, while the second axis included the theoretical framework that contained topics of semiotics, semiotic analysis, and the art of painting, as well as previous studies that dealt with the subject of analysis of works of art.